The Influence of the Availability of Work Facilities on the Work Effectiveness of Employees with Competency as Intervening Variables in the Defense Service Food and Agriculture City of Binjai - Budiman Sitepu; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2023)
This study aims to see the effect of the availability of work facilities on the work effectiveness of employees with competence as an intervening variable with associative quantitative. The population in this study amounted to 130 employees and used a saturated sample. Collecting research data using a questionnaire. The data source used is primary data. This research was conducted at the Office of Food Security and Agriculture, Binjai City. The research model used is Path Analysis and the measurement tool is Smart PLS version 3.3.3. The result of this study is that work facilities have a positive and significant effect on work effectiveness. Work Facilities have a positive and significant effect on competence. Competence has a positive and significant effect on work effectiveness.